ANALISIS NILAI TAMBAH KELAPA MENJADI KOPRA DI DESA TANDAIGI KECAMATAN SINIU KABUPATEN PARIGI MOUTONG (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
Coconut (cocos mucifera) is one of the plantation commodities that has an important role in the economy in Indonesia. In addition to contributing to Indonesia's exports, as a result of foreign exchange, as well as a source of income for coconut farmers themselves, helping the absorption of labor from the upstream to downstream sectors as well as playing a role in meeting domestic needs. Coconut is a versatile plant because all parts of the plant are useful in everyday human life. The purpose of this study was to determine the level of added value of coconuts into copra in Tandaigi Village, Siniu District, Parigi Moutong Regency. The location of this research was chosen purposively with the consideration that Tandaigi Village is one of the copra-producing areas in Siniu District, Parigi Moutong District. The study was conducted for ± 2 months from September to October 2019. The sample in this study was coconut farmers in Tandaigi Village, Siniu District, Parigi Moutong District. Determination of the sample is done by simple random sampling (simple random method). The number of samples is 123 coconut farmers who seek copra. This research uses secondary data and primary data. The results showed that the average amount of copra production produced by Coconut farmers in Tandaigi Village, Siniu District, Parigi Moutong District. An average of 16,919,000 kg / harvest season, with an average revenue of Rp. 4,289,545,455 / harvest season, the total labor cost used by farmers is Rp. 31,529,500 / harvest season. The average income earned by copra farmers is Rp. 3,353,803.03 / harvest season. Revenues are obtained by reducing total revenues and total costs used during the coconut production process into copra